ANALISIS SURVIVAL DALAM MEMPREDIKSI KONDISI FINANCIAL DISTRESS - Tyaga, Muhammad Sanyasa; Kristanti, Farida Titik (Buletin Studi Ekonomi, 2020)
Companies are required to be able to maintain the survival of the company so that the company's goals can be achieved properly. Financial distress is one of the factors that causes companies to not be able to maintain their survival so that the company's goals are not achieved. Factors that cause the company is in a state of distress are internal and external factors. This study uses internal factors such as financial ratios, size, agency costs and external factor is inflation. This research method is a quantitative method using time series data. The regression model used is the cox proportional hazard regression model. Determination of the sample using purposive sampling so that 81 samples were used in this study. Based on the results of partial tests, leverage, liquidity, activity, company size, managerial agency costs do not have a significant effect on financial distress. Only inflation has a significant positive effect on financial distress.